Fascia iliaca compartment block for hip fractures: experience of integrating a new protocol across two hospital sites. (February 2016) - Lees, Deborah; Harrison, William D.; Ankers, Thomas; A'Court, Jamie; Marriott, Allan; Shipsey, Dean; Chaplin, Andrew; Reed, Mike R.
Abstract : Objective: Fascia iliaca compartment block (FICB) administered through the loss of resistance technique effectively reduces pain and opiate requirement in elderly patients with hip fractures. FICB is a simple technique and is easily taught. This paper plots the implementation of FICB in two hospitals. Methods: A continuous audit process of two separate sites recorded the uptake of the FICB on an organizational level. An additional control group (CG) of 100 patients were analysed to compare pain scores (using the Numerical Rating Scale) and opiate requirements between groups of patients receiving fascia iliaca block and those receiving standard care. Documentation habits and adverse drug reactions were monitored over the audit process. Results: There were 434 patients audited, with 326 (75.1%) receiving the FICB. The uptake of the FICB and documentation improved over time. The FICB significantly reduced pain scores ( P <0.001) and also opiate requirement ( P <0.0001) compared with those in the CG. Acute length of stay reduced to 9.9 days (FICB group) from 15 days (CG). Inpatient mortality was 5.5% in the FICB group and 15% in the CG ( P =0.0024). Conclusion: Organizational learning of this simple procedure can be achieved through a multidisciplinary approach, and committed departmental education and feedback. The impact on length of stay and mortality were striking; however, there may be other confounding factors. Only two cases of true anaesthetic toxicity occurred in 1586 patients. The authors conclude that FICB is a safe procedure and a useful adjunct for preoperative pain control in patients with hip fractures. Abstract : Supplemental Digital Content is available in the text.